Հայերէնը Մերձաւոր Արեւելքի երկիրներուն մէջ (1918—1946) - Չոլաքեան, Յակոբ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье представлен процесс развития и обобщения западноармянского литературного языка, который начался еще до геноцида и продолжился среди разбросанных по странам Ближнего Востока армянских беженцев, где турецкий, арабский, курдский языки, а также многочисленные армянские диалекты были причиной, препятствующей национальному объединению. Армянским школам, церкви, прессе и союзам в 1918—1946 гг., до Великой репатриации, общенациональными усилиями удалось превратить западноармянский в литературный и разговорный язык, сохраняя также связь с восточно-армянским и обрядовым армянским — грабаром (древнеармянский язык). Это процесс был направлен на сохранение армянства. The article presents the process of development and generalization of the Western Armenian literary language, which began even before the Genocide and continued among the Armenian refugees scattered throughout the Middle East, where the Turkish, Arabic, Kurdish languages, as well as numerous Armenian dialects were the reason that prevented the national unification. From 1918 to 1946, before the Great Repatriation, Armenian schools, churches, press and unions, through national efforts, managed to turn the Western Armenian into a literary and colloquial language, while also maintaining a connection with Eastern Armenian and Classical Armenian (Grabar) languages. This was a process of preserving the Armenian identity.
Keywords: Բանասիրություն